Kampanye Politik di Media Online: Analisis pada situs JPNN.com dan TribunJatim.com - Rahadi Rahadi (Sospol : Jurnal Sosial Politik, 2019)
Post-reform, mass media plays an important role in political life in Indonesia. Media power in presenting or reporting political events in the form of news often has a significant impact on political developments in the country. This study focuses on political news on JPNN.com and TribunJatim.com, regarding the construction of the Governor of Deputy Governor and Deputy Governor of East Java in 2018. The researcher used Robert N Entman's framing analysis of four media analysis strategies; (1) Problem identification (2) diagnose causes (3) make moral judgment (4) treatment recommendations. The news frame carried out by JPNN.com and TribunJatim.com clearly uses the figure of Kiayi as a way to get sympathy from voters, especially those in the horseshoe and Madura region which incidentally is NU's mass base. For the East Java region outside the horseshoe and madura area (arek and matraman), the framing of the news carried out was that the candidate pairs received support from community organizations and emphasized the figure who was able to win over the problems in East Java.